Pelatihan Hantaran Pernikahan: Peningkatan Keterampilan dan Kemandirian Ibu-Ibu PKK Desa Lebosari Kecamatan Kangkung Kabupaten Kendal - Dimas Awaludin; Agustivana Mahardika; Nandita Shoffa Aulia; Arifni Intan Tsaniyatul A'tadila; Uswah Hasanah; Fadhilah Nurrochmah; Lainatul Mudzkiyyah (Jurnal Kemitraan Masyarakat, 2024)
Wedding gifts, which used to be personal and called seserahan, are now commonplace in Indonesian society and must be present at a number of wedding events. In Javanese traditional ceremonies (for example in Central Java and East Java), seserahan are usually given the night before the wedding. These wedding gifts have a very promising opportunity if made into a business. This wedding gift making training from all kinds of gifts is open to women in Lebosari Village. The delivery method is by directly providing and making materials to match the desired quality. The trainer first provides the shape of the gift, then the participants are invited to make additional shapes. Participants will also learn about statue making techniques and the tools needed to make wedding gifts. In addition, training participants also get information about the cost of making wedding gifts. The result of this training is that it can make the community more enthusiastic in filling their free time by taking advantage of existing business opportunities such as making wedding gifts.